Strategi Guru dalam Menanamkan Nilai-Nilai Multikultural pada Pembelajaran Akidah Akhlak di Madrasah Tsanawiyah - M. Kholid Thohiri; Siti Faiqotunnisa (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2021)
As a nation that has multicultural thinking and understanding, we have to be steady in accepting various cultures containing humanity values. Thus, it is a proper action to include multicultural insight in the education. Multicultural education is expected to be effective in embedding pluralism, humanism, and democratic values to the students directly. This study aims to find out what kind of strategies used by the teachers of Islamic education in embedding multicultural values in Islamic Junior High School of Al-Huda, Bandung, Tulungagung, which is explicated into three topics of focus, namely how are the multicultural values, how to plan and implement teacher strategies in instilling multicultural values, and how to know the inhibiting and supporting factors which affect the cultivating process of multicultural education values in Islamic Junior High School of Al-Huda, Bandung, Tulungagung. This is a qualitative study using descriptive approach. It uses three data collection methods, namely observation, interview and documentation. The researcher analyses the data through three components: data reduction, data display, and conclusion drawing (verification). The results of the study indicate that multicultural values embedded are the values of tolerance, mutual cooperation, mutual respect and appreciation, justice, freedom, and value of togetherness and brother-sisterhood; planning and implementation of teacher strategies is multicultural learning, various activities and habituation; the inhibiting factor of cultivation process of multicultural education values are family and culture factors, and the supporting factor are the teachers, students with critical thinking, and support from the school environment.